Factors Associated with Participation in Faith Communities for Individuals with Developmental Disabilities and Their Families - Ault, Melinda Jones (Journal of religion, disability & health, 2013)
Although disability is an unreliable predictor of the importance that spirituality and religion hold in people's lives, studies suggest faith community participation may be more limited for people with disabilities and their families. This study reports qualitative findings from a mixed-methods study exploring the perspectives of 416 parents on the welcome and support they have experienced within faith communities, both for themselves and for their sons or daughters with developmental disabilities. This study analyzed parents’ responses to open-ended survey questions, categorizing them into themes addressing factors associated with congregational participation. Key factors identified for this involvement included: (a) practices and supports provided by (or absent within) a faith community; (b) characteristics of individuals with disabilities, their parents, and faith communities; (c) attitudes and beliefs within faith communities; and (d) knowledge about persons with disabilities. Implications for supporting the full participation of people with disabilities in faith communities are discussed, as well as suggested future research directions.